COVID-19 and Cold Agglutinin Hemolytic Anemia - Maslov, Diana V.; Simenson, Victoria; Jain, Suma; Badari, Ambuga (TH Open, 2020)
Novel coronavirus disease 2019 (COVID-19) has spread throughout the world and has infected close to 4 million people. It commonly presents with fever, cough, and fatigue. Due to the high inflammatory response, it is suggested that the coagulation cascade is enhanced causing thrombotic events for many patients. We describe a patient with clinical features of cerebrovascular accident, as well as documented blood clots in bilateral upper extremities. Labs revealed the presence of cold agglutinin hemolytic anemia. The association between cold agglutinin autoimmune hemolytic anemia and thrombotic events in COVID-19 patients has not been well investigated. The patient unfortunately passed away within 48 hours after admission. This case stresses the importance of considering a full workup to diagnose autoimmune hemolytic anemia (AIHA) in COVID-19 patients with thromboses and possible implications for management.
Keywords: viral infection; thrombosis; autoantibodies